Learning Challenge: Farm Tractor Prototype with Solar Cell Technology in PjBL- STEM Learning using 4D Frame to Enhance the 21st Century Skills - Subagja, Sigit; Gunawan, Ade; Syam, Yulia Ramdinawati; Permanasari*, Anna; bin Mustam, Afian Akhbar (Universitas Syiah Kuala, 2025)
The 21st century brings many new challenges and opportunities, mainly driven by technological advancements, globalization, and a rapidly changing workforce landscape. The main goal of education is no longer academic success but also equipping students with skills called 21st century skills. The 21st century skills needed to solve complex 21st century problems such as net zero challenges. Net zero aims to achieve carbon neutrality by balancing greenhouse gas emissions and removal from the atmosphere. The research aims to develop, implement, and analyze the effects of project based learning (PjBL)-science, technology, enggineering, and mathemathics (STEM) learning on students' 21st century skills to address the net zero challenge. The research also examined how students respond to renewable energy learning using the PjBL-STEM model through a solar-powered tractor project supported by the 4D frame. This study used a conversion mixed methods approach to transform qualitative data into quantitative data using established rubrics. The results showed that PjBL-STEM learning associated with environmental issues enhances students' 21st century skills and significantly affects the teaching of students' critical thinking. Meanwhile, students showed good performance in communication, collaboration, and creativity skills through discussion activities, teamwork, presentations, and engineering desain process